2014
DOI: 10.1038/cddis.2014.326
|View full text |Cite
|
Sign up to set email alerts
|

Transcription addiction: can we garner the Yin and Yang functions of E2F1 for cancer therapy?

Abstract: Classically, as a transcription factor family, the E2Fs are known to regulate the expression of various genes whose products are involved in a multitude of biological functions, many of which are deregulated in diseases including cancers. E2F is deregulated and hyperactive in most human cancers with context dependent, dichotomous and contradictory roles in almost all cancers. Cancer cells have an insatiable demand for transcription to ensure that gene products are available to sustain various biological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 125 publications
0
56
0
Order By: Relevance
“…E2F1 encodes a member of the E2F family of TFs and plays a crucial role in a wide range of cellular processes, including cell cycle, differential, apoptosis and DNA damage [40, 41]. It had also been reported that E2F1 was deregulated in many types of cancers, such as bladder cancer, breast cancer and lung cancer [41, 42].
Figure 4Pan-cancer FFLs and their functional analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…E2F1 encodes a member of the E2F family of TFs and plays a crucial role in a wide range of cellular processes, including cell cycle, differential, apoptosis and DNA damage [40, 41]. It had also been reported that E2F1 was deregulated in many types of cancers, such as bladder cancer, breast cancer and lung cancer [41, 42].
Figure 4Pan-cancer FFLs and their functional analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…Upregulated ATF3 suppresses migration and invasion in several cancer cell types [30][31][32]; therefore, novel and specific ATF3 inducers are considered anticancer drug candidates. E2F1 transcriptionally regulates many biological functions that are deregulated in cancers [33,34]. Recent studies have reported that increased E2F1 expression causes invasion and metastasis by activating growth receptor signaling pathways and promoting an antiapoptotic tumor microenvironment [35,36].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Intriguingly, several E2F family members including E2F1 are known to be crucial for cell cycle progression and the target of tumor suppressors such as RB ( Fig. 3C) (12). We next mathematically combined the behavior of all sgRNAs targeting a specific gene in order to generate gene level scores ( Fig.…”
Section: A Pilot Clue Library Screen Detects Transcription Factors Esmentioning
confidence: 99%